Nomograms for Predicting the Incidence of Late-Onset Acute Cellular Rejection in Patients After Pediatric Liver Transplantation - Si, Zhuyuan; Dong, Chong; Sun, Chao; Wang, Kai; Zhang, Wei; Zheng, Weiping; Wei, Xinzhe; Gao, Wei; Shen, Zhongyang (Frontiers in Pediatrics, 2022)
Background Late-onset acute cellular rejection (LACR) is a special type of acute rejection (AR) only rarely studied after pediatric liver transplantation (pLT). Our study aimed to explore the influencing factors of LACR after pLT and establish a nomogram to provide an individualized prediction of LACR after pLT. Materials and Methods Data from 640 children who underwent pLT at Tianjin First Central Hospital from January 2016 to December 2019 were collected as part of this retrospective study. The nomogram was then established through the results of the multivariable analysis. Results Forty-one patients experienced LACR > 1 ≤ 2 years after pLT. Cold ischemia time, donor-specific antibodies (DSAs), and tacrolimus concentration were independent influencing factors, and a nomogram was established with an AUC value of 0.834 (95% confidence interval, 0.755–0.912). Ten-fold cross-validation showed that the accuracy of the nomogram was about 76%. Sixty-three patients experienced LACR > 2 years after pLT. Child–Pugh grade, cold ischemic time, DSAs, early acute cellular rejection, and tacrolimus concentration were independent influencing factors, and a nomogram was established with an AUC value of 0.827 (95% confidence interval, 0.774–0.881). Ten-fold cross-validation showed that the accuracy of the nomogram was about 80.9%. Conclusion We established nomograms to predict the incidence of LACR > 1 ≤ 2 and > 2 years after pLT, respectively. The verification results showed that nomograms had good accuracy and clinical practicability.